2021
DOI: 10.1177/08465371211008428
|View full text |Cite
|
Sign up to set email alerts
|

CARJ 2021: Year in Review

Abstract: The past year has been one of unprecedented challenge for the modern world and especially the medical profession. This review explores some of the most impactful topics published in the CARJ during the COVID-19 pandemic including physician wellbeing and burnout, patient safety, and technological innovations including dual energy CT, quantitative imaging and ultra-high frequency ultrasound. The impact of the COVID-19 pandemic on trainee education is discussed and evidence-based tips for providing value-added ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Because a significant amount of the professionalism topics (ethics, cultural competency, quality, and safety) are taught via didactic lectures or small-group sessions, these benefits and challenges apply to professionalism education too. Over half of the publications in our systematic literature search talked about the impact of switching to virtual learning for didactics, as a result of the COVID-19 pandemic, on resident education [ 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Although they all noted this important change in the way we provide lectures for residents, most publications showed that residents were satisfied with virtual lectures [ 11 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a significant amount of the professionalism topics (ethics, cultural competency, quality, and safety) are taught via didactic lectures or small-group sessions, these benefits and challenges apply to professionalism education too. Over half of the publications in our systematic literature search talked about the impact of switching to virtual learning for didactics, as a result of the COVID-19 pandemic, on resident education [ 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Although they all noted this important change in the way we provide lectures for residents, most publications showed that residents were satisfied with virtual lectures [ 11 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, some of these publications mentioned that residents still preferred in-person learning despite overall satisfaction with virtual learning [ 11 , 13 ]. Two articles even touted the benefits of being able to record these virtual didactic lectures, thus allowing for asynchronous learning and flipped classroom-type learning [ 11 , 12 ]. In addition, several publications pointed out that resident engagement during virtual lectures and technical difficulties can be challenging [ 11 , 14 , 18 ].…”
Section: Resultsmentioning
confidence: 99%